Water vapour source impacts on oxygen isotope variability in tropical precipitation during Heinrich events - S. C. Lewis; A. N. LeGrande; M. Kelley; G. A. Schmidt (Climate of the Past, 2010)
Water isotope records such as speleothems provide extensive evidence of past tropical hydrological changes. During Heinrich events, isotopic changes in monsoon regions have been interpreted as implying a widespread drying through the Northern Hemisphere tropics and an anti-phased precipitation response in the south. Here, we examine the sources of this variability using a water isotope-enabled general circulation model, Goddard Institute for Space Studies ModelE. We incorporate a new suite of vapour source distribution tracers to help constrain the impact of precipitation source region changes on the isotopic composition of precipitation and to identify nonlocal amount effects. We simulate a collapse of the North Atlantic meridional overturning circulation with a large freshwater input to the region as an idealised analogue to iceberg discharge during Heinrich events. An increase in monsoon intensity, defined by vertical wind shear, is modelled over the South American domain, with small decreases simulated over Asia. Simulated isotopic anomalies agree well with proxy climate records, with lighter isotopic values simulated over South America and enriched values across East Asia. For this particular abrupt climate event, we identify which climatic change is most likely linked to water isotope change – changes in local precipitation amount, monsoon intensity, water vapour source distributions or precipitation seasonality. We categorise individual sites according to the climate variability that water isotope changes are most closely associated with, and find that the dominant isotopic controls are not consistent across the tropics – simple local explanations, in particular, fall short of explaining water isotope variability at all sites. Instead, the best interpretations appear to be site specific and often regional in scale.